The effects of emotion-understanding ability and tournament incentives on supervisors’ propensity to acquire subordinate-type information to use in control decisions - Wang, Laura W. (2023)
We investigate how emotion-understanding ability, a component of emotional intelligence, and tournament incentives jointly influence supervisors' propensity to acquire information about their subordinates' trustworthiness and tailor their control decisions to this information. We predict and find that when receiving piece-rate incentives, high emotion-understanding supervisors are more likely than low emotion-understanding supervisors to acquire subordinate-type information and use it in their control decisions. In addition, relative to piece-rate incentives, tournament incentives increase supervisors’ propensity to acquire subordinate-type information more for low emotion-understanding supervisors than high emotion-understanding supervisors. Taken together, our results suggest that hiring high emotion-understanding supervisors and giving supervisors tournament incentives are at least partial substitutes in motivating supervisors to acquire and, thus, use subordinate-type information in their control decisions. Our results offer important insights into the process through which supervisors make discretionary control decisions and contribute to the understanding of the forces that shape managerial controls within organizations.